2016
DOI: 10.1038/ejcn.2016.121
|View full text |Cite
|
Sign up to set email alerts
|

Different displacement of bioimpedance vector due to Ag/AgCl electrode effect

Abstract: BACKGROUND/OBJECTIVES: Bioelectrical impedance vector analysis (BIVA) is increasingly used in clinical research to assess soft tissue hydration. It Q2 is known that physical characteristics of electrodes, such as low intrinsic impedance, low electrode/skin contact impedance and type of gel, affect the reliability of noninvasive bioimpedance assessments. The aim of this study was to determine the effect of intrinsic impedance of electrode on the bioimpedance vector displacement in RXc graph. SUBJECTS/METHODS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Nevertheless, in protocols measuring parameters before and after exercise to analyze acute vector shifts, certain factors that may generate errors in the bioelectrical signal should be controlled in order to provide accurate and reliable results, including: skin preparation [48]; previous hydration status [49]; previous consumption of food or beverage [35, 50, 51]; body position and posture during measurements [21, 51, 52]; electrode impedance [53], position and placement modification [51, 52]; time of body fluid stabilization [54, 55]; variations in cutaneous blood flow and temperature [35, 52]; skin electrolyte accumulation produced by physical exercise [35]; reproducibility of bioelectrical measurements influenced by biological intra-day [56] and inter-day variations [50]; environmental conditions [21, 52]; menstrual cycle [17, 57]; and injury condition [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in protocols measuring parameters before and after exercise to analyze acute vector shifts, certain factors that may generate errors in the bioelectrical signal should be controlled in order to provide accurate and reliable results, including: skin preparation [48]; previous hydration status [49]; previous consumption of food or beverage [35, 50, 51]; body position and posture during measurements [21, 51, 52]; electrode impedance [53], position and placement modification [51, 52]; time of body fluid stabilization [54, 55]; variations in cutaneous blood flow and temperature [35, 52]; skin electrolyte accumulation produced by physical exercise [35]; reproducibility of bioelectrical measurements influenced by biological intra-day [56] and inter-day variations [50]; environmental conditions [21, 52]; menstrual cycle [17, 57]; and injury condition [58]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a possible influence of the adhesive electrodes on the results of method comparison reproducibility for hand-to-foot BIA. It has been shown that the choice of electrodes can significantly displace bioimpedance vector positions [ 50 ]. We used the same RJL branded electrodes for measurements by both Bodystat and RJL instruments, although Bodystat does recommend the use of their own electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive contact electrode Ag/AgCl (COVIDIEN Ref. 31050522, COVIDIEN llc, Mansfield, IL, United States) with R and Xc intrinsic values of 10.89 and 0.30 Ω respectively ( Nescolarde et al, 2016 ), was chosen for L-BIA measurements. Similar to previous reports ( Nescolarde et al, 2015 , 2017 ) detector voltage electrodes (red) were placed 5 cm proximally and 5 cm distally, respectively, from the center of the injury located by US Aplio i800 (Canon Medical Systems, Japan).…”
Section: Methodsmentioning
confidence: 99%